The Role of Tax and Subsidy Policy in Driving Australian House Prices1. Issue 309 (4th March 2019) - Carrington, Sarah J.; Li, Bob; Larkin, Matthew P.
Abstract : This paper investigates the impact of tax variables and subsidy policy on real house prices, controlling for fundamental variables. The results show that the equilibrium price of housing is negatively associated with income tax rates, but positively associated with real construction costs, real land prices and the investor share in the market. House price fluctuations around their long‐run equilibrium are positively related to construction costs, land prices, and income, but negatively with income taxes. Negative gearing provisions have ambiguous effects, while stamp duty rates lack significance for house price movements on average.